A Confidence and Preparedness Survey: Cognitive Interviews for Tool Assessment and Nursing Student Perspectives - Joanne Roman Jones; Jennifer Morgan; Allison A. Lewinski; Ryan Chan; Richard Booth; Liza Behrens; Priscilla K. Gazarian (Global Qualitative Nursing Research)
Safe medication administration is a critical responsibility of registered nurses and is an essential skill developed during nursing education. Student confidence and preparation regarding medication administration are essential aspects of professional skill building. The Confidence and Preparation Survey (CPS) was used previously among homogeneous nursing student samples. The existing dominant discourse, shaped by ideologies and systems, can unfortunately lead to limited perspectives; therefore, the purpose of this study was to evaluate and refine the CPS for feasibility, clarity, and validity among nursing students primarily from groups that have been historically marginalized. A secondary purpose considered the conditions that affect perceived confidence and preparedness. Cognitive interviews were undertaken with baccalaureate nursing students ( n = 11) attending an urban college of nursing in the Northeastern region of the United States. Data were analyzed using rapid qualitative techniques and the framework matrix method. The CPS was readily understood and interpreted by this sample. Student perspectives of conditions that influence their understanding and interpretation of the CPS are described under three themes: (1) prior outside of school healthcare experiences influence understanding, (2) school experiences support survey comprehension, and (3) concerns over insufficient training within school. Findings also include a revised CPS instrument ready for further testing.